DIGITAL FINANCIAL SERVICES AND FINANCIAL INCLUSION: A STUDY OF BANKING TRANSFORMATION IN URBAN BENGALURU - S D, Kavitha Vani; Latha R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research investigates the transformative role of Digital Financial Services (DFS) in enhancing financial inclusion within the urban context of Bengaluru. As digitalisation reshapes the banking sector, particularly post-demonetisation, platforms like UPI, mobile banking, and digital wallets have redefined consumer access to financial systems. This study combines empirical data and secondary research to examine DFS usage trends, identify key barriers to adoption, and assess how effectively these innovations have advanced inclusive banking practices. The analysis reveals that while DFS offers enhanced convenience and outreach, issues such as digital literacy and cybersecurity concerns continue to limit its universal acceptance.